Examining brain structural and functional changes in mTBI with biomarkers of neurodegeneration. (20th December 2022) - Cordero, Indira Ruth Garcia; Vasilevskaya, Anna; Taghdiri, Foad; Khodadadi, Mozhgan; Tator, Charles; Mikulis, David; Tarazi, Apameh; Mushtaque, Asma; Colella, Brenda; Green, Robin; Tartaglia, Carmela
Abstract: Background: Mild traumatic brain injury (mTBI) in former contact sports athletes is a risk factor for dementia. However, it is unknown why only some individuals with mTBI develop dementia, suggesting that head injury exposure alone is not sufficient to produce the condition. We hypothesize that mTBI could be associated with neurodegenerative processes that target specific brain structures and connectivity networks and increase vulnerability to dementia. Method: 46 male former professional athletes with a history of multiple concussions were recruited. To compare participants with evidence of underlying pathology versus participants without any evidence, the sample was divided into neurodegenerative biomarker positive (N+, n = 25) and negative (N‐, n = 21) groups. The division was based on the positivity in at least one of these biomarkers: cerebrospinal fluid total tau (> 300 pg/ml), cortical positron emission tomography tau standardized uptake value ratio (>1.30) and serum neurofilament light‐chain (> 12.5 pg/ml). Groups were matched for age and number of concussions. Cognitive profiles were assessed by comparing the following scores between groups: Trail Making Test ratio, Digit Span Backwards, Paced Auditory Serial Addition Test, verbal fluency, and Rey Auditory Verbal Learning Test (RAVLT). Grey matter volume was calculated by voxel‐based morphometry and compared between groups. Functional connectivity differences were evaluated for the default mode (DMN), the salience (SN) and the dorsal attention (DAN) networks. Results: (N+) presented more number of intrusions at immediate ( p = 0.04, FDR corrected) and short delay recall ( p = 0.02, FDR corrected) and worse recognition discrimination index ( p = 0.02, FDR corrected) in the RAVLT in comparison to (N‐). In addition, (N+) displayed more atrophy in the left frontal superior and middle gyrus ( p < 0.001, extended threshold = 50 voxels) and disconnection of the DAN ( p < 0.001, FWE cluster correction) versus (N‐). No significant differences were obtained for the DMN and SN. Conclusion: Frontal atrophy and DAN abnormal connectivity may underlie cognitive deficits in the (N+) group. Biomarkers of neurodegeneration provide a sensitive tool to detect participants with structural and functional changes and may associate with higher risk to develop dementia after mTBI.